Rancang Bangun Media Pembelajaran Interaktif Mata Pelajaran Penerapan Rangkaian Elektronika Menggunakan Canva - Rahma Dhina Syifa Ananda; Hendra Hidayat (MASALIQ, 2026)
Although the use of digital technology in learning continues to develop, the development of interactive learning media that meet the valid and practical criteria for the topic of Sensor and Transducer Circuits still requires attention. This study aims to design and produce interactive learning media based on the Canva application that meet the valid and practical criteria for eleventh-grade students of Audio Video Engineering at SMK Negeri 5 Padang. This study employed a research and development method using the 4-D model, which includes the Define, Design, Develop, and Disseminate stages. Product validation was carried out by two material experts and two media experts, while the practicality test involved 20 students. The results showed that the assessment by the material experts obtained a score of 93.74% in the “Very Valid” category, while the assessment by the media experts reached 96.87% and was also included in the “Very Valid” category. In the practicality test, the learning media obtained a score of 96.92% in the “Very Practical” category. These findings indicate that the developed Canva-based interactive learning media are feasible and appropriate to be integrated into the learning process. This study contributes to the development of digital learning media that support the effectiveness of vocational learning, particularly on the topic of Sensor and Transducer Circuits.